Video-based methodologies: the affordances of different viewpoints in understanding teachers' tacit knowledge of practice that supports young children's oral language. Issue 5 (20th October 2018) - Nolan, Andrea; Paatsch, Louise; Scull, Janet
ABSTRACT: Using video as a mode of data generation in research involving young children and their teachers has become a more common practice in educational research. Digital video recordings provide the opportunity to capture the complexity of interactions that occur between people, time, space and objects, however, working with this methodology and form of data can be complex and challenging. This paper focuses on the use of video as a methodology to understand teachers' tacit knowledge of practice that supports young children's oral language. This study explores four specific viewpoints that have been employed to investigate teachers' practice: (1) camera, (2) teacher, (3) researcher and (4) peers. From our analysis of the affordances of the differing viewpoints, we propose that what can be 'seen' is directly impacted by the understandings of those involved in the research process in relation to data capture, viewing and analysing the data. We argue that these viewpoints are not neutral or mutually exclusive rather they should be considered complementary and supplementary in building a comprehensive understanding of teachers' tacit knowledge of literacy practice.